The Influence of Leadership Style, Job Training, and Compensation on Employee Job Satisfaction and Work Motivation as Intervening Variables: Pengaruh Gaya Kepemimpinan, Pelatihan Kerja, dan Kompensasi Terhadap Kepuasan Kerja Karyawan dan Motivasi Kerja Sebagai Variabel Intervening - Harviani, Nidah Emi; Harjatno, Slamet (Indonesian Journal of Innovation Studies, 2022)
This research is a type of quantitative research with hypothesis testing. The sample used in this study were all employees of CV Bintang Tex Indonesia as many as 85 employees. The sampling technique used the total sampling method (saturated sampling). The analytical tool used in this study is a path analysis technique with the help of software for an operating system called Smart-PLS (Partial Least Square) Version 3.0. The data used in this study are questionnaire data and data sourced from CV Bintang Tex Indonesia. Data collection techniques using questionnaires, interviews, and observations. The results of this study prove that Hypothesis 1: Training and Compensation Variables have a significant effect on Job Satisfaction, while Leadership Style has no significant effect on Job Satisfaction. Hypothesis 2: Leadership Style Variable has a significant effect on Work Motivation, while Compensation has no significant effect on Work Motivation. Hypothesis 3: The leadership style variable has a significant effect on job satisfaction through work motivation as an intervening variable, while job training has no significant effect on job satisfaction through work motivation as an intervening variable, and compensation has no effect on job satisfaction through work motivation as an intervening variable.